2003
DOI: 10.15369/sujms1989.15.21
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology in Diabetic Patients with Fecal Incontinence

Abstract: : The aim of this study was to investigate the pathophysiology of fecal incontinence in patients with diabetes mellitus. Methods. Two groups of diabetic patients were studied. Group A consisted of 7 subjects (48 to 76 years, mean age 53.5 years) with fecal incontinence and Group B consisted of 9 subjects (38 to 79 years, mean age 62

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…26,29 Parks et al 30 demonstrated that there was histologic evidence of denervation in the external anal sphincter muscle in patients with fecal incontinence and rectal prolapse, and suggested that this may be the result from pudendal neuropathy occurring as a consequence of rectal descent induced during repeated defecation straining. 32 The present series also showed the increased PNTML in patients with rectal prolapse, even if PNTML was measured only in eight patients compared with that in the control subjects (median, 2.0 ms [1.8-2.2]) reported in our previous study, 33 suggesting that pudendal neuropathy may occur in those patients. 31,32 Similarly, PNTML was significantly increased in incontinent patients with rectal prolapse.…”
Section: Discussionsupporting
confidence: 73%
“…26,29 Parks et al 30 demonstrated that there was histologic evidence of denervation in the external anal sphincter muscle in patients with fecal incontinence and rectal prolapse, and suggested that this may be the result from pudendal neuropathy occurring as a consequence of rectal descent induced during repeated defecation straining. 32 The present series also showed the increased PNTML in patients with rectal prolapse, even if PNTML was measured only in eight patients compared with that in the control subjects (median, 2.0 ms [1.8-2.2]) reported in our previous study, 33 suggesting that pudendal neuropathy may occur in those patients. 31,32 Similarly, PNTML was significantly increased in incontinent patients with rectal prolapse.…”
Section: Discussionsupporting
confidence: 73%
“…The pudendal nerves, on the other hand, are somatic nerves that innervate the EAS. Diabetic pudendal neuropathy leads to delay of pudendal nerve terminal motor latency, causes EAS damage, and may result in FI [28]. Our results suggest that somatic neuropathy plays a more important role in FI in diabetic patients.…”
Section: Open Accessmentioning
confidence: 58%